Adsorption removal of arsenic from aqueous solutions and groundwater by isomeric FeOOH. (22nd September 2022) - Xiong, Huixin; Xu, Shimeng; Zhu, Shibei
Abstract: FeOOH as a naturally abundant, relatively low-cost and effective adsorbent have been gradually valued in wastewater field rich in arsenic pollution, which can make for environmental remediation. In this study, FeOOH samples included Gth1/Gth2 as goethite, Aka1/Aka2 as akaganéite, and Lep as lepidocrocite, were prepared and used as adsorbents, and adsorption kinetic and isotherm experiments of As(III) were analyzed. Meanwhile, the effects of pH, adsorbent content, arsenic initial concentration and electrolyte solutions on adsorption processes were also discussed in detail to study adsorption behaviors and mechanism. The results showed that As(III) could be effectively adsorbed on goethite, akaganéite and lepidocrocite, the adsorption equilibrium achieved after 24 h. When As(III) concentration ranged in 40 mg/L, the saturated adsorption amounts (mg/g) calculated by the Langmuir equation were 12.3 (Gth1), 7.50 (Gth2), 6.29 (Aka1), 23.4 (Aka2), and 17.7 (Lep). The increase of adsorbent and adsorbate levels was favorable to improve the adsorption capacities of As(III) within a certain range. Removal efficiency of As(III) with Na2 SO4 and NaH2 PO4 as electrolyte reduced by about 10% and 30%, respectively. Therefore, the appropriate parameters in the adsorption process for investigation were isomeric FeOOH of 1.0 g/L, pH 7.0 and NaNO3 as electrolyte. In simulated groundwater filter system initially with 200 μg/L of arsenic species at about pH 7.0, arsenic removal strength for five FeOOH adsorbents (0.8 g) was Aka2 > Aka1 and Gth1 > Lep and Gth2. Some differences were present in the infrared (IR) spectra of arsenic-loaded and original isomeric FeOOH. These outcomes could give the aim at seeking high efficient materials for the purification of arsenic contaminated groundwater and put out the suggestion. HIGHLIGHTS: Five isomeric FeOOH samples were used for arsenic removal. The adsorption kinetic and isotherm experiments of As(III) were analyzed. Akaganeite of Aka2 had the highest adsorption capacity to As(III). Graphical Abstract